The Analysis of Brand Extension Reputation on the Intention in Choosing Private University in Indonesia - Evi Sofia; Lilik Noor Yuliati; Hartoyo Hartoyo; Agus W. Soehadi (STAI Hubbulwathan Duri, 2022)
Brand reputation is important when choosing an education. Universities that already have a brand reputation can more easily attract prospective new students. There is a phenomenon where Private Universities are using extended brand reputation to compete. The purpose of this research is to analyze the impact of brand extension reputation on the intention in choosing private universities. The quantitative research method of Structural Equation Modeling uses a structured questionnaire. The questionnaires have been distributed to the students, and have been completed by email. It is a self-administrated method. The survey was conducted on students at one of Aperti (Aliansi Perguruan Tinggi) BUMN (Badan Usaha Milik Negara) with a total sample of 400 respondents using quota sampling. The results showed that the parent brand of BUMN had a significant influence on the extended brand of Aperti BUMN, which impacted student intention when choosing the university. Brand extension reputation has an indirect effect on intention through output expectation